Development of relationships between permeability coefficient and electrical and thermal conductivity of recycled aggregates permeable cement concrete. (10th September 2020) - Wang, Hui; Zhang, Ailian; Shi, Feiting; Liu, Junzhe; Cao, Peng; Du, Tao; Gu, Haoran
Highlights: Influence of rheological parameters on permeability of permeable cement concrete is studied. Evaluation functions for the electrical resistance, compressive strength and permeability coefficient have been proposed. Evaluation function for thermal conductivity and permeability coefficient is obtained. Abstract: Relationships between electrical, thermal conductivities, compressive strength and penetration of permeable cement concrete with various rheological parameters are investigated in this paper. Water-cement ratios applied in this research are 0.3, 0.35 and 0.4. Various dosages of polycarboxylate superplasticizer are used to adjust the fresh paste to different rheological properties. Results show that the evaluation function for rheological parameters (slump flow and plastic viscosity) and permeability coefficient fits well with a linear function. Meanwhile, the evaluation functions for the electrical resistance, compressive and permeability coefficient have been proposed and the correlation has been deduced as one dimensional Gauss function equation. Furthermore, the evaluation function for thermal conductivity and permeability coefficient is obtained from this research. Permeability coefficient presents a downward trend with the increasing slump flow and decreasing plastic viscosity. A reasonable equivalent circuit diagram is selected to reveal the conductive mechanism of permeable cement concrete (consisted of the contact resistance in specimen and its embedded electrodes and the following series-connected electrical components). Additionally, higher water-cement ratio with larger fluidity and lower plastic viscosity shows a worse permeability coefficient.